2016
DOI: 10.3892/etm.2016.3263
|View full text |Cite
|
Sign up to set email alerts
|

Potential implications of interleukin-7 in chronic wound healing

Abstract: Methods of identifying chronic wounds that will heal in a timely, coordinated fashion and those that will not, together with novel therapeutic strategies, are vital for progression in the field of wound healing. Interleukin (IL)-7 has been associated with various biological and pathological processes. The present study explored the potential role of IL-7 in wound healing. IL-7 expression levels were examined in a clinical cohort of chronic wounds using reverse transcription-quantitative polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…The rationale for selecting IL‐7, a lymphopoietic cytokine produced in thymus and BM, is based on its potential role in cell survival, proliferation, and differentiation processes . It also plays important role in chronic wound healing where it is produced by skin keratinocytes . In our study, we have also observed the presence of IL‐7 protein in rat skin keratinocytes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The rationale for selecting IL‐7, a lymphopoietic cytokine produced in thymus and BM, is based on its potential role in cell survival, proliferation, and differentiation processes . It also plays important role in chronic wound healing where it is produced by skin keratinocytes . In our study, we have also observed the presence of IL‐7 protein in rat skin keratinocytes.…”
Section: Discussionsupporting
confidence: 55%
“…The present study was conducted to assess the effect of IL‐7 transfected rat bone marrow (BM) MSCs on diabetic wound healing both in vitro and in diabetic wound model in vivo. Based on its role in proliferation, cell survival, and cellular differentiation processes, as well as in wound healing, it is expected that these genetically modified MSCs would improve wound healing potential of MSCs.…”
mentioning
confidence: 99%
“…[75][76][77] Furthermore, the pro-inflammatory cytokines that showed increased expression in the current study (IL-6, IL-7, IL-8) have been implicated as significant mediators in wound healing and similar diseases that involve resolution of inflammatory events. [78][79][80] Additionally, when looking at the duration of hMSC viability from our previous study, we observed that the hMSCs are only viable for the first ~9 days post-injection, thus the hMSCs likely respond to the local environment to help induce a local endogenous response which could have longer lasting therapeutic effects, particularly if it promoted the resolution of chronic inflammation. 18 While encapsulated hMSCs elicited a pro-inflammatory response in the current study, they also secreted anti-inflammatory cytokines and chemokines which may have therapeutic potential.…”
Section: Biomaterials Encapsulation Of Hmscs Induced a Targeted Paracrmentioning
confidence: 97%
“…(11,12) Using the impedance sensor, we can observe the cytotoxicity of a variety of toxicants and the status of stem and cancer cells. (13)(14)(15)(16)(17)(18)(19) When cells are added to the electrical cell-substrate impedance sensor array and attached to the electrodes, they act as insulators that increase the impedance. As the cells grow and cover the electrodes, the number, shape, and attachment properties of these cells affect the current flow and change the impedance.…”
Section: Introductionmentioning
confidence: 99%